Multi-voxel coding of stimuli, rules, and responses in human frontoparietal cortex. - Woolgar, A; Thompson, R; Bor, D; Duncan, J (2011)
In human functional magnetic resonance imaging (fMRI), a characteristic pattern of frontal and parietal activity is produced by many different cognitive demands. Although frontoparietal cortex has been shown to represent a variety of task features in different contexts, little is known about detailed representation of different task features within and across different regions. We used multi-voxel pattern analysis (MVPA) of human fMRI data to assess the representational content of frontoparietal cortex in a simple stimulus-response task. Stimulus-response mapping rule was the most strongly represented task feature, significantly coded in a lateral frontal region surrounding the inferior frontal sulcus, a more ventral region including the anterior insula/frontal operculum, and the intraparietal sulcus. Next strongest was coding of the instruction cue (screen color) indicating which rule should be applied. Coding of individual stimuli and responses was weaker, approaching significance in a subset of regions. In line with recent single unit data, the results show a broad representation of task-relevant information across human frontoparietal cortex, with strong representation of a general rule or cognitive context, and weaker coding of individual stimulus/response instances.